PENGARUH LITERASI KEUANGAN DAN PERILAKU EKONOMI TERHADAP PENGELOLAAN KEUANGAN MAHASISWA PENERIMA BEASISWA KIP-KULIAH PENDIDIKAN EKONOMI FKIP UNTAN - Wulan, Sari; Husni Syahrudin; Syamsuri (Universitas Tanjungpura, 2026)
This study investigates the impact of financial literacy and economic behavior on financial management. Using a correlational research design with a quantitative approach, this study focuses on a population of 43 scholarship recipients enrolled in the Economics Education program at FKIP Untan, specifically from the 2021-2024 cohorts. The research sample used non-probability sampling techniques with a census/total sampling method involving 43 students. The analysis methods used in this study included descriptive statistics, T-test, Ftest, multiple linear regression, and coefficient of determination. The results of the study show that: 1) financial literacy (X1) has a significant partial effect on financial management (Y); 2) economic behavior (X2) has a significant partial effect on financial management (Y); and 3) there is a simultaneous effect of financial literacy (X1) and economic behavior (X2) on financial management (Y). The coefficient of determination calculated is 0.564, indicating that the contribution of variable X1 and variable X2 in explaining or predicting variable Y is 56.4%. Future researchers are encouraged to explore a wider range of variables, including lifestyle factors, pocket money, income, and other relevant influences.